FLOWERING LOCUS T2 Promotes Shoot Apex Development and Restricts Internode Elongation via the 13-Hydroxylation Gibberellin Biosynthesis Pathway in Poplar - Gómez-Soto, Daniela; Allona, Isabel; Perales, Mariano (Frontiers in Plant Science, 2022)
The adaptation and survival of boreal and temperate perennials relies on precise demarcation of the growing season. Seasonal growth and development are defined by day length and temperature signals. Under long-day conditions in spring, poplar FLOWERING LOCUS T2 (FT2) systemically induces shoot growth. In contrast, FT2 downregulation induced by autumnal-short days triggers growth cessation and bud set. However, the molecular role of FT2 in local and long-range signaling is not entirely understood. In this study, the CRISPR/Cas9 editing tool was used to generate FT2 loss of function lines of hybrid poplar. Results indicate that FT2 is essential to promote shoot apex development and restrict internode elongation under conditions of long days. The application of bioactive gibberellins (GAs) to apical buds in FT2 loss of function lines was able to rescue bud set. Expression analysis of GA sensing and metabolic genes and hormone quantification revealed that FT2 boosts the 13-hydroxylation branch of the GA biosynthesis pathway in the shoot apex. Paclobutrazol treatment of WT leaves led to limited internode growth in the stem elongation zone. In mature leaves, FT2 was found to control the GA 13-hydroxylation pathway by increasing GA2ox1 and reducing GA3ox2 expression, causing elevated GA1 levels. We here show that in poplar, the FT2 signal promotes shoot apex development and restricts internode elongation through the GA 13-hydroxylation pathway.